O trabalhador do complexo psiquiátrico no “país das maravilhas”: Burnout, sobrecarga, satisfação laboral e autoestima - Pascoal, Francilene Figueirêdo da Silva (2019)
Introduction: Psychiatric institution workers deal with patients with severe mental disorder and often with poor working and organizational conditions that can generate overload, dissatisfaction, low self-esteem and consequently develop burnout. This research emerged as a proposal to understand the psychosocial phenomenon that involves burnout in this service. Objective: To analyze burnout, workload, job satisfaction and self-esteem in workers at a Psychiatric Complex (CP) located in the city of João Pessoa - PB. Method: A cross-sectional, qualitative and quantitative study with 188 workers. The research instruments were: Sociodemographic Questionnaire Cuestionario para la Evaluación del Síndrome de Quemarse por el Trabajo; Labor Impact Assessment Scale, Work Satisfaction Questionnaire, and Self-Esteem Scale. Data were collected between September 2017 and April 2018 at the CP, after approval by the Ethics and Research Committee - CAAE: 77103317.0.0000.5188. The data of the quantitative approach were analyzed by the statistical program PSPP 1.0.1. Descriptive statistical analyzes were performed considering means, Standard Deviations and Pearson correlation between variables. The reliability of the scales was tested with Cronbach's alpha measure. Responses regarding the descriptive issues of the Impact Scale were processed by Software IRAMUTEQ and submitted Content Analysis. Results: 4% (N = 7) of the participants with a characteristic burnout condition, low Workload (M = 1.41, SD = 0.48), medium satisfaction (M = 3.55, SD = 0.91) and high self-esteem (M = 33.69, SD = 3.95). There was a negative correlation of burnout with self-esteem and job satisfaction, while there was a positive association with the labor impact. In the qualitative analysis, two categories emerged - "Aspects of Work Overload" and "Strategies / recommendations to reduce overload". Conclusion: There was burnout illness in the sample studied, although it revealed low overload, medium satisfaction and satisfactory self-esteem, which indicates that other characteristics need to be investigated and that seem to reduce the occurrence of Burnout Syndrome. As noted in this paper, despite all the difficult conditions, the workers seem to see themselves in Lewis Carroll's Land of Wonders.